2007
DOI: 10.1149/1.2719644
|View full text |Cite
|
Sign up to set email alerts
|

SEI Layer Formation on Amorphous Si Thin Electrode during Precycling

Abstract: The morphological and compositional changes of the solid electrolyte interphase (SEI) layer formed on the surface of Si thin electrodes during precycling were investigated. At the beginning of charging, the native layer ( SiO2 and silanol) covering the surface of the Si thin electrode is readily destroyed and a new SEI layer is formed by the decomposition of both organic solvents and anions. At this stage, the interfacial resistance decreases to a minimum level. Thereafter, the interfacial resistance increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
152
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(157 citation statements)
references
References 12 publications
5
152
0
Order By: Relevance
“…For the most lithiated phase, the shift has been found to be slightly below -2 eV for Si2p electrons. Similar peak shifts can also be observed in earlier PES studies on Si electrodes [7][8][9][10]16]. Observations of changes in peak position due to state of charge for graphite electrodes has also recently been presented and discussed as a result of changes in chemical environment and/or changes in work function [36].…”
Section: Binding Energy Variations Associated With Sei Formation or Csupporting
confidence: 67%
See 1 more Smart Citation
“…For the most lithiated phase, the shift has been found to be slightly below -2 eV for Si2p electrons. Similar peak shifts can also be observed in earlier PES studies on Si electrodes [7][8][9][10]16]. Observations of changes in peak position due to state of charge for graphite electrodes has also recently been presented and discussed as a result of changes in chemical environment and/or changes in work function [36].…”
Section: Binding Energy Variations Associated With Sei Formation or Csupporting
confidence: 67%
“…A lot of work has been done to understand the SEI on graphitic negative electrodes while the field of SEI formation on silicon is still a young area with only a rather small number of publications. [4,[7][8][9][10][11][12][13][14][15][16][17][18][19] Philippe et al have…”
Section: Introductionmentioning
confidence: 99%
“…The charge (lithiation) plateau at 0.8 V in the first cycle is ascribed to the SEI layer formation. 29,30) The plateau locations during both lithiation and delithiation are also consistent with the aforementioned CV data as well as previously reported values. The Coulombic efficiency in the first cycle turns out to be 63%.…”
Section: The Characterization Of Sinp-cnt Compositessupporting
confidence: 91%
“…5, the thermal evolution at approximately 140 o C is related to the particle size, the thermal evolution at approximately 140 o C increases with decreasing particle size for fully lithiated Si electrodes. Since the thickness of a solid electrolyte interface (SEI) layer on an Si film anode increases with lithiation 7 and more SEI film is formed in the electrode with a smaller particle size, it is suggested that the thermal evolution at approximately 140 o C is mainly due to the thermal decomposition of the SEI film. The major exothermic peak is significantly reduced and shifted to the lower temperature side as the Si particle size decreases.…”
Section: Methodsmentioning
confidence: 99%